The Effect of Rational Emotive Behaviour Therapy on Work-irrational Beliefs Among Electrical and Electronic Educators in Nigeria - Iliya, Nungse Nuhu; Chinyere Ogbuanya, Theresa; O. I. Okeke, Chinedu (Journal of Technical Education and Training, 2023)
This study delved into a critical concern in academic and professional settings: the impact of irrational work-related beliefs among individuals within the Electrical/Electronic Technology Education domain in Nigeria. The prevalence of detrimental work-related beliefs and their potential adverse effects on performance, mental health, and overall well-being necessitated an investigation into effective therapeutic interventions to mitigate these beliefs. The research adopted a quasi-experimental design spanning eight weeks and involving 16 sessions to examine the effects of Rational Emotive Behavioural Therapy (REBT) on these work-related irrational beliefs. The study encompassed a cohort of 330 participants, comprising Electrical/Electronic Technology Education technologists and instructors within Nigerian universities. To ensure a robust study design, the participants were randomly allocated to the REBT group (165 participants) or the control group (165 participants). The study uncovered notable findings using an intervention package and structured psycho-educational strategies for data collection. The analysis revealed a significant mean difference between the experimental (REBT) group and the control group, demonstrating the efficacy of REBT in significantly reducing work-related belief scores among Electrical and Electronic Technologists compared to those not exposed to the therapy. Furthermore, the study explored potential variations based on gender in response to the treatment, finding that the interaction effect of therapies and gender was not statistically significant. This suggests that the benefits of REBT in alleviating work-related irrational beliefs were consistent across genders. These findings underscore the potential of REBT as an effective intervention to address work-related irrational beliefs. The study recommends the integration of REBT into the academic curriculum, emphasising its value in mitigating detrimental work-related beliefs among educational staff and students in the field of Electrical/Electronic Technology Education.